Molecular pathogenesis and treatment of cavernous nerve injury-induced erectile dysfunction: A narrative review - Song, Guoda; Hu, Peng; Song, Jingyu; Liu, Jihong; Ruan, Yajun (Frontiers in Physiology, 2022)
Introduction: Erectile dysfunction (ED) is a common complication after radical prostatectomy (RP), and it seriously affects the quality of life in patients and their partners. The primary trigger of postoperative ED is surgical injury to the cavernous nerves that control penile erection and run along the anterolateral aspect of the prostate. Despite the introduction and ongoing innovation of nerve-sparing techniques, a significant number of patients still suffer from moderate cavernous nerve injury (CNI), which is thought to be transient and reversible. Therefore, early postoperative penile rehabilitation therapy may salvage patients' erectile function by promoting cavernous nerve regeneration and preventing penile structural alterations. Aims: To present a comprehensive overview of the current molecular pathogenesis of CNI-induced ED, as well as novel therapeutic strategies and their potential mechanisms. Methods: A literature search was performed using PubMed. Search terms included erectile dysfunction, cavernous nerve injury, pathogenesis, pathway, and treatment. Results: The NOS/NO pathway, oxidative stress-related pathway, RhoA/ROCK pathway, transforming growth factor-β(TGF-β), sonic hedgehog (Shh), and hydrogen sulfide (H2S) are involved in the molecular pathogenesis of CNI-induced ED. Multiple neurotrophins, including brain-derived nerve growth factor (BDNF), glial cell line-derived neurotrophic factor (GDNF), and neurturin (NTN), were found to promote cavernous nerve regeneration. Emerging therapeutic approaches can be roughly summarized into four categories, namely small molecule and drug, stem cell-based therapy (SCT), micro-energy therapy and platelet-rich plasma (PRP) therapy. Conclusions: These pathways collectively lead to the irreversible damage to the penile structure after CNI. The combined early rehabilitation strategies of promoting upstream nerve regeneration and recovering abnormal molecular signals of downstream penis are presumed to save patients’ erectile function after RP. In future studies, the cross-talk between these molecular pathways needs to be further clarified, and the questions of how denervation injury induces the molecular alterations in the penis also need to be addressed.